Effect of cardiorenal syndrome and its different subtypes on incidence of atrial fibrillation in a nationwide analysis. (19th May 2022) - Fauchier, L; Bisson, A; Maisons, V; Bodin, A; Herbert, JM; Angoulvant, D; Halimi, JM; Lip, GYH
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiorenal syndromes (CRS) are associated with increased risks of all-cause and cardiovascular death, end-stage kidney disease (ESKD), myocardial infarction (MI), heart failure (HF) and ischemic stroke. Whether CRS (and different subtypes of CRS) are more prone to develop atrial fibrillation (AF) is unclear. Methods: This longitudinal cohort study was based on the national hospitalization database covering hospital care from the entire French population. The analysis focused on those with at least 5 years of complete follow-up (or dead earlier) as described by others. We identified 439, 787 consecutive patients hospitalized in France in 2012 who had heart failure (HF), chronic kidney disease (CKD) and/or CRS. We estimated incidences of clinical events (including incident AF) during follow-up. Analysis were adjusted for 1) age and sex and 2) all baseline characteristics except cardiac and renal comorbidities. Results: Overall, 58.2% were male, 67.7% had hypertension, 31.6% had diabetes mellitus and their mean age was 75.3±13.2; 329, 154 had isolated HF, 67, 939 had isolated CKD, 15, 695 had acute concomitant CRS (which could be type 1, 3 or 5 CRS), 15, 699 had type 2 CRS (cardiorenal) and 11, 300 had type 4 CRS (renocardiac). History of AF was present in 36.4 % of the patients: 39.9% in those with isolated HF, 13.3% in those with isolated CKD, 43.0% in those with concomitant CRS, 57.2% in those with type 2 CRS, 35.3% in those with type 4 CRS (overall p<0.0001). Incidence and adjusted hazard ratios for of all-cause death, cardiovascular death and incident AF are in Table 1. CRS was associated with a higher risk of death and patients with type 2 CRS had the highest risk of all-cause and cardiovascular mortality. Isolated HF was associated with a higher risk of incident AF than isolated CKD (Table 1). Patients with CRS had higher risk of incident AF than those with isolated HF or isolated CKD. Among patients with CRS, those with concomitant CRS had the numerically highest 5-year risk of incident AF, which was not statistically different than those with type 2 or type 4 CRS in adjusted analysis. Conclusion: The long-term prognosis of CRS subtypes is poor and may vary, some CRS subtypes being more closely associated with risk of all-cause death and cardiovascular mortality than others. Risk of incident AF is higher in CRS than in isolated HF or isolated CKD and is not statistically different among the various subtypes of CRS.